The influence of Lake Erie on changes in temperature and frost dates. (5th March 2020) - Dobson, Kara C.; Beaty, Lynne E.; Rutter, Michael A.; Hed, Bryan; Campbell, Michael A.
Abstract: Anthropogenic climate change is affecting virtually all ecosystems across the globe. Some of the noticeable effects of the changing climate are the shifting of frost dates in the fall and spring, and how warm temperatures are distributed throughout the year. The degree to which an ecosystem is affected by these changes depends upon many factors, including where the ecosystem is located and what regional variabilities in climate surround that ecosystem. One ecosystem that experiences a unique microclimate is the region surrounding Lake Erie, the southernmost Laurentian Great Lake. Using historic climate data dating from 1948 to 2017, we set out to determine how changes in temperature and frost dates differ between the coastal and inland regions of the southern coast of Lake Erie, and to hypothesize as to why these effects may be occurring differently between these regions. We found that, for both coastal and inland regions, the first frost in the fall has begun later, while the last frost in the spring has begun earlier, leading to both regions experiencing longer frost‐free seasons. However, although both regions have experienced these shifts, the rate at which these shifts occurred differed between the coastal and inland regions. The average date that the frost events occurred also differs between the two regions. It was also found that average temperatures have been increasing for each region, primarily in coastal regions, due to increased minimum temperatures over time. The results from this study highlight the importance of regional climate variability in large‐scale climatic studies. Abstract : The degree to which an ecosystem is affected by changes in climate depends upon many factors, including where the ecosystem is located and what regional variabilities in climate surround that ecosystem. Using historic climate data dating from 1948 to 2017, we set out to determine how changes in temperature and frost dates differ between coastal and inland regions of Southern Lake Erie, and to hypothesize as to why these effects may be occurring differently between these regions.